2016
DOI: 10.1016/j.antiviral.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The E119D neuraminidase mutation identified in a multidrug-resistant influenza A(H1N1)pdm09 isolate severely alters viral fitness in vitro and in animal models

Abstract: Keyword: Influenza A(H1N1)pdm09 Resistance Neuraminidase E119D Zanamivir a b s t r a c tWe recently isolated an influenza A(H1N1)pdm09 E119D/H275Y neuraminidase (NA) variant from an immunocompromised patient who received oseltamivir and zanamivir therapies. This variant demonstrated cross resistance to zanamivir, oseltamivir, peramivir and laninamivir. In this study, the viral fitness of the recombinant wild-type (WT), E119D and E119D/H275Y A(H1N1)pdm09 viruses was evaluated in vitro and in experimentally-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…While the impact of the framework H275Y and E119G substitutions on the resistance phenotype to NAI is well documented [12], the effect of the remaining NA substitutions at residues 94, 95 and 287 has not been reported. We found no impact of these residues on NA expression and/or activity using recombinant proteins [20] (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the impact of the framework H275Y and E119G substitutions on the resistance phenotype to NAI is well documented [12], the effect of the remaining NA substitutions at residues 94, 95 and 287 has not been reported. We found no impact of these residues on NA expression and/or activity using recombinant proteins [20] (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, viral cultures could not be obtained for the two double mutants suggesting attenuating effects [11, 12]. The role of the H275Y-E119D change in altering viral fitness was further confirmed both in vitro and in animal models [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although subtypespecific NA mutations conferring resistance to NAIs and oseltamivir-resistant variants (the H275Y mutation in NA) have been reported previously (6,(18)(19)(20), no laninamivirresistant mutations from clinical samples have been reported (8,10,21). However, some viruses, generated by reverse genetics, containing (i) known NA mutations in an A(H1N1)pdm09 virus (e.g., E119G, E119V, and Q136K) conferring reduced to highly reduced inhibition by laninamivir (8,22,23) and (ii) novel mutations (e.g., I427T [24], I436N [25], and E119D [26]) conferring various degrees of inhibition by NAIs have been described. Nevertheless, the possible emergence of laninamivir resistance should be considered, making the identification of amino acid substitutions conferring resistance to NAIs from in vitro studies valuable in helping elucidate the mechanisms of resistance and predicting clinical cases of resistance to this class of antivirals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that a multidrug-resistant influenza A(H1N1)pdm09 virus harbouring an E119D neuraminidase (NA) amino acid substitution (N2 numbering is used throughout for influenza A NA residues) arose in an immunocompromised patient after 17 days of zanamivir therapy [11]. Using reverse genetics, multiple studies have shown that recombinant influenza A(H1N1)pdm09 virus with the E119D NA mutation can confer resistance to multiple NAIs, such as zanamivir, oseltamivir and peramivir [12,13]. However, the genetic stability and replication fitness of the E119D variant differed across the two studies [12,13].…”
Section: Selection Of Multi-drug Resistant Influenza a And B Viruses mentioning
confidence: 99%
“…Using reverse genetics, multiple studies have shown that recombinant influenza A(H1N1)pdm09 virus with the E119D NA mutation can confer resistance to multiple NAIs, such as zanamivir, oseltamivir and peramivir [12,13]. However, the genetic stability and replication fitness of the E119D variant differed across the two studies [12,13].…”
Section: Selection Of Multi-drug Resistant Influenza a And B Viruses mentioning
confidence: 99%